The kinematic analysis of the trunk and weight-bearing symmetry in the three planes of movement during the four phases of sit-to-stand in adults with stroke and a community control group - case-control study - Steyn, Hesti (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScPhysio)--Stellenbosch University, 2018.